The History of Parliament - Seaward, Paul (History compass, 2003)
Since 1951 the History of Parliament has been at work on one of the most complex and comprehensive projects ever attempted in British history. In its fifty years the History has published just eight works: but they include two hundred and eighty-one years’ worth of political and parliamentary life in twenty-eight volumes, twenty-one thousand pages, around seventeen million words; over eighteen thousand biographies and around two thousand three hundred constituency articles researched in exhaustive detail, pulled together with introductory surveys.